ANALISIS RELEVANT COST TERHADAP PENGAMBILAN KEPUTUSAN MENGGANTI ATAU MEMPERTAHANKAN AKTIVA TETAP (STUDI KASUS PADA CV. PYRAMID MULTI BLOCK MANADO) - Klaas, Athalia Girly Debora; Poputra, Agus T.; Pinatik, Sherly (Universitas Sam Ratulangi, 2015)
Many methods costs incurred to assist companies in making decisions. One of the so-called cost relevant cost. Relevant costs are future costs that differ among alternatives exist, and the costs that can be avoided. Relevant information depends on decisions made. Relevant cost can affect a company manager's decision to take the right decision. One of them is a decision to replace or maintain the assets owned by the company.The purpose of this study was to determine and analyze the application of the concept of relevant costs in the decision to replace or maintain the assets. This research was conducted at CV. PYRAMID MULTI BLOCKÂ is located at Jalan Yos Sudarso No. 116 Kairagi Weru, Manado. The company is an industrial company that produces paving stone / block. The object of this study is the fixed assets in the form of Multi Block machine SB-306 is the company's main production machine. The method used in this research is descriptive method is a method that collects, formulate and classify and interpret the data obtained by the analysis of quantitative data presented in the form of numbers that are relevant cost analysis of the revenue and costs incurred.The results showed that the role of the relevant cost analysis can assist management in the decision to replace or maintain the assets. By looking at the development of profit between the two alternatives to replace or maintain fixed assets such as machinery Multi Block SB - 306, it can be seen that it would be more profitable for the company to replace the old fixed assets such as machinery Multi Block SB - 306 with the new machine.